(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to determine the empowerment of women. The research used was a qualitative research method with a descriptive type of research. This research is the Head of Panincong Village, Chairperson, Treasurer, Secretary of the Women Farmers Group (KWT), and the Community. Data collection techniques using observation, interviews, and documentation. The validity of the data was obtained through source triangulation and technical triangulation. Data analysis techniques through data collection, data reduction, data presentation, and drawing conclusions. The results showed that the process of empowering women through the KWT program based on the results of the research conducted had been going well where the planning and implementation indicators had been met but the evaluation indicators were not met where the level of achievement of goals in the women’s empowerment process did not go well.